To study the impact of glycemic control over cardiac autonomic neuropathy in type 1 and type 2 diabetics patients using bedside tests at a tertiary care hospital - Anjum, Sumaiya; K., Suresh (International Journal of Advances in Medicine, 2017)
Background: Cardiac autonomic neuropathy a serious complication of diabetes and is often overlooked. It is associated with higher cardiovascular mortality and poor quality of life in diabetic individuals. The Glycemic control has been well established as the risk factor for all the diabetes related microvascular and macrovascular complications. This stresses importance of role of glycemic control over CAN in Type 1 and Type 2 Diabetics in order to stop further progression to advanced and irreversible stages. The objective was to study the impact of various demographic and other clinical factors over prevalence of CAN in type 1 and type 2 diabetic patients who are asymptomatic for CAN using bedside tests Methods: A case control comparative clinical study was undertaken comprising of 100 diabetic patients, both type 1 and type 2 with duration from 5-10 years and >10 years. The tests which were performed are deep breathing test, heart rate response to standing, hand grip test, cold pressor test, BP response to standing. Depending on these tests, patients were categorised as patients with cardiac autonomic neuropathy and without cardiac autonomic neuropathy. Results: The prevalence of cardiac dysautonomia was 68%. Type 2 diabetics had higher prevalence of cardiac dysautonomia than type 1 diabetics (p=0.025). Significant correlation was observed between cardiac autonomic neuropathy and poor glycemic status (type 1 p<0.001; type 2 p<0.001). The mean HbA1c in patients with and without CAN in type 1DM was 9.16+0.81 and 7.21+0.56 and in type 2 DM was 9.15+1.72 and 7.15+0.53 respectively. Similarly, presence of other microvascular complications increased the prevalence of CAN in both types of diabetes mellitus. Conclusions: Cardiac autonomic neuropathy is a common complication in long standing diabetes. Present results suggest that glycemic status of the diabetics is undoubtedly an important factor for the onset of cardiac dysautonomia which in turn account for high prevalence of cardiac mortality in diabetic patients. All asymptomatic diabetic patients should be evaluated for the presence of autonomic neuropathy and glycemic status should be controlled to prevent the further progression of CAN.